Synergy of educational institutions, industry, and government in the absorption of workforce of vocational high school graduates in Kendal industrial park, Kendal regency - Rara Ratih Pratiwi; Yulekhah Ariyanti; Windi NR Wardhani (Universitas Wahid Hasyim Semarang, 2022)
AbstractThis study is carried out to synergize academics, entrepreneurs, and government both central and regional, as it is expected to contribute to the decrease of unemployment rate in Central Java. This study is conducted in Kendal Special Economic Zone in Kendal Industrial Park (KIP) using the collaboration of the three actors with Triple Helix that is considered able to increase creativity, ideas, and skills. In this study, triple helix is used as an analytical knife to bridge the gap between job seekers and employers.This study aims to describe and analyze the role of Triple Helix in increasing skills and competence of the society in fulfilling labor qualification required by the KIP as well as the synergy of educational institutions, industry, and the government in decreasing the number of employment of vocational high school graduates in Kendal Regency. The method used in this study is qualitative approach. The location or research object is in Kendal Industrial Park in Jalan Raya Arteri KM. 19, Brangsong, Kendal Regency, Central Java, 51371. The results of this study explain that the interaction between industry and academics gives rise to the exploratory innovation capabilities of the company with the Triple Helix framework. In Triple Helix I (static regime), it shows that the government of Kendal Regency plays the main role in regulating university and industry. In Triple Helix II (laissez-faire regime), Kendal Industrial Park becomes the driver for university and government. In Triple Helix III (trilateral-hybrid organization), the university become the active actors in the cooperative relationship between government and industry in a balanced interaction model. From this results, it can be concluded that the Triple Helix synergy enable the increase of the absorption of vocational high school graduates from Kendal Regency in Kendal Industrial Area.It occurs with the cooperation between university and industry, along with the mentoring in Kendal Industrial Park using “SCORE” training. Besides, cooperation between the government and university also occur with human capital training and development for vocational high school graduates, which include improvement culture, work planning problem solving, cost control system development, and self-development program. Cooperation between government, university, and industry result in a digital-based application development called “Si Lamar”, which brings job seekers and industry together. This will ease vocational high school graduates to find suitable job, and help industry to carry out the recruitment process